ALQURAN DALAM PERDEBATAN PEMAHAMAN TEKSTUAL DAN KONTEKSTUAL - Sadik, M. (Hunafa: Jurnal Studia Islamika, 2009)
The Qurâan, the holy scripture of the Muslims, never changes since itsÂ  revelation. However, qurâanic exegesis, as the results of brilliant thoughts of the interpreter can only differ from one another. The difference of qurâanic exegesis may be brought about by methods of interpreting the qurâanic verses. Generally speaking, there are method of interpreting the qurâanic verses; textual interpretation and contextual interpretation. These two methods of interpretation have been employed from the time of the Prophet Muhammad to the present time.Kata Kunci: Alquran, pemahaman tekstual, pemahaman kontekstual